Ragam Metode Pembelajaran Pendidikan Agama Islam - Putri, Ferlinda Tiara; Suhaeni, Heni (Al-Khazin: Jurnal Pendidikan Agama Islam, 2025)
Islamic Religious Education (PAI) plays a significant role in shaping students’ character and moral values. To achieve these goals, selecting appropriate teaching methods is essential for enhancing the effectiveness of the learning process. This study is categorized as library research, conducted by reviewing various reference books and scholarly journals related to the topic. The aim of this research is to identify commonly used PAI teaching methods and analyze their strengths and weaknesses. The methods discussed include lecturing, discussion, question-and-answer, demonstration, and project-based learning. Each method has distinct characteristics that influence learning outcomes in the cognitive, affective, and psychomotor domains. Based on the review, no single method is entirely perfect; each has advantages that can be optimized and limitations that educators must consider. Therefore, PAI teachers should be able to choose and combine various methods flexibly according to the context, learning material, and student characteristics. This study is expected to serve as a reference for educators in designing more effective and engaging PAI learning strategies.